The Effect of Live Yeast Probiotics in Lactation Diets with and without a Yeast Prebiotic in Nursery Diets on Lifetime Growth Performance, Antibody Titers, and Carcass Characteristics - Abigail K. Jenkins; Joel M. DeRouchey; Jordan T. Gebhardt; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Joseph A. Loughmiller; Brian T. Kremer (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 28 mixed parity sows (Line 241 DNA) and their offspring were used in a farrow-to-finish study to evaluate the effect of live yeast supplementation during lactation with or without yeast extract supplementation during the nursery period on sow and litter performance and lifetime growth performance, serum antibody titers, and carcass characteristics. Sows were blocked by parity and BW on d 110 of gestation and allotted to 1 of 2 dietary treatments which consisted of a standard corn-soybean meal lactation diet with or without yeast-based probiotics (0.10% Actisaf Sc 47 HR+; Phileo by Lesaffre, Milwaukee, WI). Following weaning, a total of 350 pigs (241 × 600 DNA; initially 13.5 ± 0.05 lb) were randomly assigned within sow treatment to 1 of 2 nursery diets which consisted of a control diet or a diet that contained yeast prebiotics (0.10% MS309; Phileo by Lesaffre, Milwaukee, WI) for 42 d after weaning (d 59 of age). After this time, two nursery pens of the same treatment were combined into one finishing pen and pigs were fed common diets until market. There were no significant effects of live yeast supplementation on lactation performance (P>0.079). A sow × nursery diet interaction (P= 0.024) was observed during the nursery period where pigs from sows fed Actisaf had improved ADG when fed the control nursery diet compared to pigs from control sows that were fed the control nursery diet. Pigs fed MS309 in the nursery from either sow treatment were intermediate. Pigs from Actisaf sows tended to be heavier at marketing (P= 0.067) with heavier HCW (P= 0.101) but there were no differences in overall finishing growth performance with the inclusion of live yeast in lactation diets or yeast prebiotics in nursery diets (P>0.100). Subsets of pigs were bled on d 22, 38, 50, 66, 78, 101, and 162 of age to determine porcine circovirus type 2 (PCV2) andMycoplasma hyopneumoniaeantibody sample-to-positive (S/P) ratios and on d 50, 66, 78, 101, and 162 of age to determine the percent inhibition ofLawsonia intracellularis. An S/P ratio is representative of antibodies present in the blood for that specific pathogen. There was a tendency for a sow diet × day interaction for the PCV2 S/P ratio (P= 0.097) where offspring from sows fed live yeast had higher PCV2 S/P ratios at 101 d of age compared to offspring from control sows (P= 0.046). There was a nursery diet × day interaction for the PCV2 S/P ratio (P= 0.036) where pigs fed MS309 during the nursery period had reduced PCV2 S/P ratios at 66, 78, and 162 d of age (P<0.022). In conclusion, feeding a yeast prebiotic in the nursery did not affect performance or immune parameters. Conversely, feeding a live yeast probiotic during lactation resulted in a tendency to improve ADG during the nursery period, final BW, and numerically improve HCW.
Keywords: antibody titers; live yeast; yeast probiotics; nursery pig